Diet and dental pathology : A comparative study between the inhabitants of late dynastic Dakhleh Oasis and the Nubians - Tamer Gad Rashed; Moheb Mohamed Shaaban (Cairo : Tamer Gad Rashed, 2013)
The present study examined eight dietary, pathological and occupational dental indicators in the Ein-Tirghi, Dakhleh Oasis skeletal population. The sample consisted of 198 skulls (97 males and 101 females) that dated back to the late Dynastic period (1070-404 B.C.). Moreover, relevant published data on the Nubians were used for comparison
Thesis (Ph.D.) - Cairo University - Institute of African Research and Studies - Department of Anthropology
Issued also as CD
Keywords: Dental pathology; Diet; Ein Tirghi